Recalibrating populism measurement tools: Methodological inconsistencies and challenges to our understanding of the relationship between the supply- and demand-side of populism - Olivas Osuna, José Javier; Rama, José (Frontiers in Sociology, 2022)
The analysis of the congruence between the demand- and supply-side of populism is key to understand the relationship between citizens and populist parties, and to what extent this is mainly a “pull” or “push” phenomenon. Although the study of populism has experienced an unprecedented growth across social sciences during the last decade, research directly addressing this connection remains scarce. Moreover, most existing tools used to measure populism have not been created paying much consideration to their compatibility with those applied in the other side of this demand-supply divide. This article critically revisits the influential Comparative Study of Electoral Systems (CSES) Module 5 dataset to illustrate shortcomings regarding current efforts to measure the demand- and supply-sides of populism. We show that according to CSES data the, often presumed, correspondence between “populist” attitudes and likelihood of voting for “populist parties” is only partial and country specific. But more importantly, we identify three main potential sources of such mismatch linked to instrumental issues: (i) problems with the choice, design and operationalization of attitudinal survey items; (ii) problems in the assessment of parties’ populism; and (iii) instrument biases that make them more effective with some varieties of populism than with others. These methodological limitations are hindering our ability to settle longstanding theoretical debates concerning the correspondence between the demand- and supply-side, the relative centrality of attributes, and varieties of populism. Therefore, we invite scholars working in this field to update existing measurement tools, or develop new ones, considering the multidimensionality of this latent construct, the diversity of movements, and the need to apply consistent criteria and operationalization techniques when assessing degrees of populism in citizens and parties.